If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + s) + -8 = 2s + -23 Remove parenthesis around (6 + s) 6 + s + -8 = 2s + -23 Reorder the terms: 6 + -8 + s = 2s + -23 Combine like terms: 6 + -8 = -2 -2 + s = 2s + -23 Reorder the terms: -2 + s = -23 + 2s Solving -2 + s = -23 + 2s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2s' to each side of the equation. -2 + s + -2s = -23 + 2s + -2s Combine like terms: s + -2s = -1s -2 + -1s = -23 + 2s + -2s Combine like terms: 2s + -2s = 0 -2 + -1s = -23 + 0 -2 + -1s = -23 Add '2' to each side of the equation. -2 + 2 + -1s = -23 + 2 Combine like terms: -2 + 2 = 0 0 + -1s = -23 + 2 -1s = -23 + 2 Combine like terms: -23 + 2 = -21 -1s = -21 Divide each side by '-1'. s = 21 Simplifying s = 21
| k*k-8=-7 | | 6x+8x-x=-5x | | -1.6(b-3.35)=-11.28 | | 3(x^2)-2+2Sinx=0 | | 2(m+4)=3(m-1) | | 4x^3+3x^2=7x | | 25(2x+1)3+10(2x+1)2-35(2x+1)= | | 2e^3x=-3 | | 12867=x+.467 | | -6=-4+2s | | P=29+2w | | b+b=-6 | | 4r^3+10r^2-6r=0 | | 9+v=v+6 | | 5y-8-3y+2=10 | | 3(1+8x)=-117 | | 4.20*12= | | -11x+1y=-13 | | 6x-4*6=-24 | | 6+2x-2x^2=0 | | 48+3a=7a | | 7t-7=-14 | | 3x+y^4=-y^8 | | 2x+3*x=65 | | 4+3x+4+3x+x+6+x+6=32 | | 5.7+0.3x=6.9 | | X+3x+(3x+4)=101 | | 48+3a=a | | 3x^5-2x^3+7=0 | | -9=-9y+18 | | -10.6-7y=14 | | x+3/2+4/3=x+17/6-x/2 |